Metode Pengembangan Social Question Pada Anak Dalam Perspektif Pembimbing - Wijio, Sarono (Universitas Nusantara PGRI Kediri, 2020)
Social intelligence is currently seen as a determining factor for a child's success in education. The purpose of this study is to describe the social intelligence of children and methods for developing children's social intelligence. This type of research is qualitative descriptive which is directly carried out on the object under study in order to produce the necessary data and to answer the problem formulation, namely: how is the supervisor's understanding of social intelligence in children and the guidance method in directing children to develop social intelligence in Kindergarten Pembina I Putussibau. Data collection was carried out by interviewing, observing, and documenting the research data sources which included: supervising teachers at Kindergarten Pembina I Putussibau, students, brochures, and curriculum. The qualitative descriptive method was used as data analysis by means of the available data being processed during the next research to be systematically interpreted into reports. It is known that the research results are as follows: 1) The supervisor's understanding of social intelligence in children is that social intelligence is the ability shown by children when interacting with other people or the social environment. 2) The method used by the supervisor in practically developing children's social intelligence is with individual and group guidance, while theoretically, the approach used by the supervisor is the cognitive and social learning approach from Albert Bandura.